Optimizing Family Financial Stability Through Islamic Household Accounting Practices : A Literature Review - Yani, Ahmad; Purwanti, Lilik (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the importance of accounting practices in household financial management, focusing on creating budgets, recording transactions, and systematic financial planning to achieve long-term financial goals. Through literature analysis, this research shows that effective accounting practices can optimize resource allocation, reduce the risk of excessive debt, and increase financial literacy. As a result, families can make more informed and responsible financial decisions, supporting the establishment of a positive financial culture that contributes to the economic well-being of society. In the context of an Islamic family, financial management not only regulates household finances but also forms a strong and fair economic foundation, in line with spiritual and moral values. This research offers valuable insights for families and policymakers in supporting household financial sustainability